Building better products with finite element analysis - Adams, Vince, 1963- (OnWord Press, 1999)
This book is divided into four parts: Introduction to FEA and the analytical method; Finite element modeling basics; Advanced modeling techniques and applications; and Integrating simulation into product design strategy.